Long-term outcome and complications of acute correction of canine antebrachial deformities with patient-specific three-dimensional printed osteotomy and reduction guides in 15 dogs - Tzimtzimis, Emmanouil; Rutherford, Scott (Frontiers in Veterinary Science, 2025)
ObjectiveTo describe the owner-perceived long-term outcome and complications following acute correction of antebrachial deformities in dogs using patient-specific, three-dimensional (3D)-printed osteotomy and reduction guides and internal fixation.MethodsRetrospective study of 15 dogs (20 limbs). Medical records of dogs with antebrachial deformities corrected using patient-specific 3D-printed osteotomy/reduction guides and internal fixation with bone plates and a minimum of 1 year of owner follow-up were reviewed. Data collected included patient and surgical details, perioperative, short-, mid-, and long-term outcomes, as well as complications. Pre-surgical planning involved Computer-Aided Design (CAD) subjective segment orientation, from which patient-specific osteotomy and reduction guides were created.ResultsAll but one (19/20) limb had full function, and one limb had acceptable function at a mean owner follow-up time of 23 months. The mean long-term Liverpool Osteoarthritis in Dogs (LOAD) and Canine Orthopedic Index (COI) scores were 4.4 and 3.5, respectively. The only minor complication was the breakage of the ulnar plate (1 limb). There were two types of major (I) complications: surgical site infection (3/20 limbs, 15%) and implant-related soft tissue irritation (4/20 limbs, 20%), both of which were treated successfully with implant removal. There were no intraoperative, major (II) or catastrophic complications.Clinical significanceThe acute correction of canine antebrachial deformities aided by patient-specific, 3D-printed osteotomy and reduction guides resulted in excellent long-term outcomes. Complications encountered were surgical site infection and implant-related soft tissue irritation. All complications were successfully treated.